PTU-201 The endoscopic cost of bariatric surgery. (28th May 2012) - Steed, H; Golar, H; Manjunath, S
Abstract : Introduction: Complication rates of Roux-en-Y gastric bypass (REYGB) vary from centre to centre, but anastomotic stricture is the commonest and is managed in the majority by endoscopic pneumatic dilatation. This study aimed to assess the endoscopic costs of REYGB surgery. Methods: All patients undergoing REYGB surgery over a 29-month period were included (553) and were followed up retrospectively and prospectively for a minimum of 180 days to monitor for endoscopic procedures performed in relation to the REYGB. Results: 113 patients had 147 endoscopic procedures, including 65 pneumatic dilatations, at a cost to the endoscopy department of £58 077 over a 29 month study period, with an average cost of £2003 a month or £105 per REYGB operation performed. One patient required three dilatations, two required six dilatations and the rest were dilated once, using a range of 11 mm to 16 mm balloons at the endoscopists discretion. Five patients had completely occluded anastomoses. The anastomotic stricture rate for the group was 11.39%. Three patients had acute ulceration at the anastomosis, giving a symptomatic ulcer rate of 0.7%. The delay in time from surgery to dilatation ranged from 4-5-6 days, with a mean of 94 days. 60% of anastomotic strictures occurred within 3 months, 78% within 4 months, 92% within 5 months and 95% within 6 months. Conclusion: If bariatric surgery is performed locally then endoscopy departments must expect to factor in, not only the costs of dealing with actual complications, but also the cost of investigating for potential complications. The average cost to the endoscopy department per REYGB procedure performed is £105. Competing interests: None declared.